2012
DOI: 10.11336/jjcrs.3.37
|View full text |Cite
|
Sign up to set email alerts
|

Discharge index and prediction for stroke patients in the post-acute stage: Evaluation of the usefulness of Nichijo-seikatsu-kino-hyokahyo

Abstract: Iwai N, Aoyagi Y. Discharge index and prediction for stroke patients in the post-acute stage: Evaluation of the usefulness of Nichijo-seikatsu-kino-hyokahyo. Jpn J Compr Rehabil Sci 2012; 3: 37-41. Introduction:The objective of this study was to evaluate whether or not the Nichijo-seikatsu-kinohyokahyo could be used as an index for predicting ADL independence level or discharge destination. Method: The subjects were 482 patients extracted from the Japanese Association of Rehabilitation Medicine Patient Databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 0 publications
3
6
2
Order By: Relevance
“…The range of duration from onset of stroke to admission was 8-60 days, length of hospital stay was 22-180 days, and FIM score at admission was 18-119 (Table 1). The basic attributes of the subjects were similar to those in the nationwide survey [8] and the report of Iwai et al [3], except for the shorter duration from onset of stroke to admission. The subjects were divided into two groups by FIM score at admission: group A consisted of 102 patients with scores of 18-58 and group B consisted of 154 patients with scores of 59-119 .…”
Section: Methodssupporting
confidence: 67%
See 3 more Smart Citations
“…The range of duration from onset of stroke to admission was 8-60 days, length of hospital stay was 22-180 days, and FIM score at admission was 18-119 (Table 1). The basic attributes of the subjects were similar to those in the nationwide survey [8] and the report of Iwai et al [3], except for the shorter duration from onset of stroke to admission. The subjects were divided into two groups by FIM score at admission: group A consisted of 102 patients with scores of 18-58 and group B consisted of 154 patients with scores of 59-119 .…”
Section: Methodssupporting
confidence: 67%
“…Iwai et al [3] created a prediction equation for FIM score at discharge using four items: age, days from onset of stroke to admission, motor FIM at admission, and cognitive FIM at admission, as explanatory variables (R 2 =0.675). The addition of NSKH score to this prediction equation resulted in an increase in R 2 (0.719) of 0.044.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of previous studies investigating the home discharge of stroke patients have indicated that social factors including age, NIHSS, ADL at hospitalization and discharge (degree of paralysis and level of required nursing care), whether oral nutrition is possible, and family aspects as well as rehabilitation intervention units are factors that contribute to home discharge for stroke patients [4,[10][11][12][13][14]. hospitalization, and long-term caregiving ability (evaluated on a scale from 1-5) [14]. In their study, no limitations were placed on age of stroke patient, and it was reported that age was a direct predictive factor for discharge to home.…”
Section: Discussionmentioning
confidence: 99%